The standard form of a quadratic equation is
,
where
,
, and
are coefficients. You want to get the given equation into this form. You can accomplish this by putting all the non-zero values on the left side on the equation.
In this case, the given equation is
![5x^{2}+2=4x](https://tex.z-dn.net/?f=5x%5E%7B2%7D%2B2%3D4x)
Since
is on the right side of the equation, we subtract that from both sides. The resulting equation is
![5x^{2}-4x+2=0](https://tex.z-dn.net/?f=5x%5E%7B2%7D-4x%2B2%3D0)
Looking at the standard form equation
, we can see that
![a=5, b=-4, c=0](https://tex.z-dn.net/?f=a%3D5%2C%20b%3D-4%2C%20c%3D0)